Leishmania donovani infection enhances lateral mobility of macrophage membrane protein which is reversed by liposomal cholesterol. - Moumita Ghosh; Koushik Roy; Dipanwita Das Mukherjee; Gopal Chakrabarti; Kingshuk Roy Choudhury; Syamal Roy (Public Library of Science (PLoS), 2014)
The protozoan parasite Leishmania donovani (LD) reduces cellular cholesterol of the host possibly for its own benefit. Cholesterol is mostly present in the specialized compartment of the plasma membrane. The relation between mobility of membrane proteins and cholesterol depletion from membrane continues to be an important issue. The notion that leishmania infection alters the mobility of membrane proteins stems from our previous study where we showed that the distance between subunits of IFNγ receptor (R1 and R2) on the cell surface of LD infected cell is increased, but is restored to normal by liposomal cholesterol treatment.We determined the lateral mobility of a membrane protein in normal, LD infected and liposome treated LD infected cells using GFP-tagged PLCδ1 as a probe. The mobility of PLCδ1 was computationally analyzed from the time lapse experiment using boundary distance plot and radial profile movement. Our results showed that the lateral mobility of the membrane protein, which is increased in infection, is restored to normal upon liposomal cholesterol treatment. The results of FRAP experiment lent further credence to the above notion. The membrane proteins are intimately linked with cellular actin and alteration of cellular actin may influence lateral mobility. We found that F-actin is decreased in infection but is restored to normal upon liposomal cholesterol treatment as evident from phalloidin staining and also from biochemical analysis by immunoblotting.To our knowledge this is the first direct demonstration that LD parasites during their intracellular life cycle increases lateral mobility of membrane proteins and decreases F-actin level in infected macrophages. Such defects may contribute to ineffective intracellular signaling and other cellular functions.